The Differences in Communication Ability and Mathematical Disposition of Students who are given a Geogebra- Assisted Contextual Learning Model and the Cooperatif Learning Model - Khairani Syahfitri; Mulyono Mulyono; Pargaulan Siagian; Else Frine Tamba (BIRCU, 2021)
This study aims to: (1) analyze the differences in mathematical dispositions between students who are given a contextual learning model assisted by Geogebra and students who are given a model of cooperatif learning assisted by Geogebra at SMK Harapan Mekar 1 Medan, (2) analyze the interaction between learning and early mathematics ability (high, moderate, low) students towards improving students' mathematical communication skills at SMK Harapan Mekar 1 Medan, (3) analyzing the interaction between learning and the initial mathematics ability (high, medium, low) of students towards improving the mathematical disposition of students at SMK Harapan Mekar 1 Medan. The population of this study were all students of SMK Harapan Mekar 1 Medan in class X majoring in Automotive Mechanics and Computer Engineering. Samples were taken randomly from 6 classes, Students were selected as a sample of 2 classes, namely class X-2 as the experimental class I which was given the contextual learning model assisted by Geogebra and class X-3 as the experimental class 2 which was given the cooperative learning model assisted by Geogebra, with a total of 64 students. Data were analyzed using descriptive statistical analysis through two-way analysis. The results of this study indicate that: (1) There are differences in mathematical communication skills between students who are given a contextual learning model assisted by Geogebra and students who are given a cooperative learning model, (2) there are differences in mathematical disposition between students who are given a contextual learning model assisted by Geogebra and students who given a cooperative learning by Geogebra.